Junction Field‐Effect Transistors Based on PdSe2/MoS2 Heterostructures for Photodetectors Showing High Responsivity and Detectivity. (4th September 2021) - Wang, Haoyun; Li, Zexin; Li, Dongyan; Xu, Xiang; Chen, Ping; Pi, Lejing; Zhou, Xing; Zhai, Tianyou
Abstract: 2D materials have shown great promise for next‐generation high‐performance photodetectors. However, the performance of photodetectors based on 2D materials is generally limited by the tradeoff between photoresponsivity and photodetectivity. Here, a novel junction field‐effect transistor (JFET) photodetector consisting of a PdSe2 gate and MoS2 channel is constructed to realize high responsivity and high detectivity through effective modulation of top junction gate and back gate. The JFET exhibits high carrier mobility of 213 cm 2 V −1 s −1 . What is more, the high responsivity of 6 × 10 2 A W −1, as well as the high detectivity of 10 11 Jones, are achieved simultaneously through the dual‐gate modulation. The high performance is attributed to the modulation of the depletion region by the dual‐gate, which can effectively suppress the dark current and enhance the photocurrent, thereby realizing high detectivity and responsivity. The JFET photodetector provides a new approach to realize photodetectors with high responsivity and detectivity. Abstract : A junction field‐effect transistor (JFET) photodetector based on PdSe2 /MoS2 is demonstrated with high responsivity (6 × 10 2 A W −1 ) and high detectivity (10 11 Jones), which is realized by effective dual‐gate modulation. The JFET photodetector provides a new approach to realize photodetectors with high responsivity and detectivity.